Agriecoepidemiology of Trypanosomosis due to Trypanosoma vivax in ruminants of some farms located in Venezuela: Technical note - Tamasaukas, Rita; Ruiz, Héctor; Aguirre, Aixa; Roa, Noris; Cobo, Margarita; Aso, Pedro María (Revista Científica de la Facultad de Ciencias Veterinarias)
Results obtained of seroprevalence of T. vivax in ovine and bovine farms located in two counties of Aragua State (Camatagua and San Casimiro) and one of Guárico State (Roscio), as well as the determination of trypanosomosis agriecoepidemiology. Concluding that the values of seroprevalence were smaller during the dry season in comparison with the rainy season, evidencing a marked relationship with the season and to the agroecological zone.